Pengaruh Kualitas Produk, Citra Merek Dan Kepercayaan Merek Terhadap Keputusan Pembelian Layanan Internet Telkom Indihome - Sebayang, Fabillah Isna Farah; Nst, Amrin Mulia Utama (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of Product Quality, Brand Image and Brand Trust on the Purchase Decision of Telkom Indihome Internet Services on customers in Tanjung Sari Village. This study uses associative research, namely research that aims to determine the relationship between two or more variables, where the variables are measured using a Likert scale. This study uses a sample of users or customers who use Telkom Indihome Internet Services in Tanjung Sari Village with a sample of 87 people. Based on the results of the study, it was concluded that Product Quality (X1), Brand Image (X2) and Brand Trust (X3) together (simultaneously) have a significant influence on the Purchase Decision of Telkom Indihome Internet Services on customers in Tanjung Sari Village